2019
DOI: 10.3892/or.2019.7154
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the clinical significance and prospective molecular mechanisms of cystatin genes in patients with hepatitis B virus‑related hepatocellular carcinoma

Abstract: The present study aimed to investigate the clinical significance and prospective molecular mechanism of cystatin (CST) genes in patients with hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). The role of CST genes in the molecular mechanism of HCC was revealed through bioinformatics analysis. The clinical significance of CST genes was investigated using GSE14520-derived data from patients with HBV-related HCC. Gene set enrichment analysis (GSEA) was used to identify pathways in which the CST gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The cystatins consist of three families of proteins that bind reversibly with high-affinity to inhibit multiple cathepsin family members ( 8 ) Cystatin F is unique among the cystatins in that its expression is limited to leukocytes ( 9 ) and because it is secreted in an inactive form that can be internalized and subsequently activated in target cells ( 10 , 11 ). In the context of malignancy, increased levels of CST7 have been correlated with a poorer prognosis in liver metastasis following colorectal cancer ( 12 ) and with improved survival in the context of pancreatic ductal adenocarcinoma ( 13 ) and hepatocellular carinoma ( 14 ). Additionally, in the context of neuroinflammation, CST7 is upregulated during CNS demyelination and is associated with areas of remyelination ( 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cystatins consist of three families of proteins that bind reversibly with high-affinity to inhibit multiple cathepsin family members ( 8 ) Cystatin F is unique among the cystatins in that its expression is limited to leukocytes ( 9 ) and because it is secreted in an inactive form that can be internalized and subsequently activated in target cells ( 10 , 11 ). In the context of malignancy, increased levels of CST7 have been correlated with a poorer prognosis in liver metastasis following colorectal cancer ( 12 ) and with improved survival in the context of pancreatic ductal adenocarcinoma ( 13 ) and hepatocellular carinoma ( 14 ). Additionally, in the context of neuroinflammation, CST7 is upregulated during CNS demyelination and is associated with areas of remyelination ( 15 , 16 ).…”
Section: Resultsmentioning
confidence: 99%
“…If neutrophilic cystatin F is secreted, then it may act to suppress cathepsin C in other cells. Furthermore, if cystatin F is secreted by neutrophils in a tumor microenvironment ( 14 ), then it may contribute to pro-tumor immunosuppression. We identified a dataset (GSE101584) for tumor-associated neutrophils in a mouse cancer model ( 29 ) and found a significant increase in CST7 expression compared to that in naïve neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Survival analysis indicated that CST6 correlated with the OS and recurrence-free survival (RFS) of patients with hepatitis B virus-related hepatocellular carcinoma (HBV-related HCC) [ 116 ]. CST6 may function as a prognostic biomarker for HCC, with a high CST6 expression being associated with poor survival of patients, in correlation with a previous report claiming that cystatin M/E could be a pancreatic tumor promotor [ 119 ].…”
Section: Tumor-promoting Role Of Cystatin M/ementioning
confidence: 99%
“…CST6 may function as a prognostic biomarker for HCC, with a high CST6 expression being associated with poor survival of patients, in correlation with a previous report claiming that cystatin M/E could be a pancreatic tumor promotor [ 119 ]. Taken together, data suggest that cystatin M/E may participate in diverse molecular mechanisms and exert distinct effects in different types of cancer [ 116 ].…”
Section: Tumor-promoting Role Of Cystatin M/ementioning
confidence: 99%
“…In CRC cells, p53-induced upregulation of CST5 promoted the induction of mesenchymal-epithelial transition [34]. Recently, CST5 had been shown to inhibit the proliferation, migration, and tumor formation of xenografted CRC cell lines [35], as well as exhibit higher expression levels in hepatocellular carcinoma tissue compared to normal tissue [36]. Thus, CSTs cannot be merely regarded as a cysteine protease inhibitor considering its vital role in tumorigenesis.…”
Section: Ivyspringmentioning
confidence: 99%